Robert B. Koehl (ed.). Studies in Aegean Art and Culture. A New York Aegean Bronze Age Colloquium in Memory of Ellen N. Davis. - Dickinson, Oliver (Journal of Greek Archaeology, 2017)
This is a publication, in paperback format, of papers that were mostly presented at a special session of the New York Aegean Bronze Age Colloquium, held to honour the memory of Ellen Davis. Although her output was not very extensive, it included studies of considerable importance apart from her magnum opus on Aegean Bronze Age vessels of precious metal, and several of the papers are clearly intended to complement these studies and carry them further. The papers vary considerably in length, in breadth of topic, and in the amount of illustration provided, but all have something interesting to say.